Intake Ground Vortex Aerodynamics - Murphy, John (Cranfield University, 2008)
When an aircraft is operating in static or near static conditions during taxiing or take-o a vortex can form between the ground and the intake. With engine diameters increasing, intakes are moving non-dimensionally closer to the ground and as a consequence the likelihood of vortex formation during the aircraft operating envelope is set to increase. To date there is little quantitative knowledge therefore a greater understanding is required. This research is aimed at providing an extensive quantitative parametric study of vortex formation leading to advanced design rules for future engines. A 1/30 th scale generic model intake was operated in the Cranfield University 8 ′ × 6 ′ wind tunnel to examine ground vortex formation under quiescent, headwind and crosswind conditions. Stereoscopic Particle Image Velocimetry and total pressure measurements have been extensively taken to assess the external and internal flowfields. For the first time experiments with a rolling ground plane have been performed to provide insight into the formation and characteristics of ground vortices during take-o . As the velocity ratio reduces a characteristic trend is established whereby the vortex is initially weak, increases in strength to a local maximum and reduces to zero thereafter. The operating points that generate the strongest vortex for a given configuration have been determined and an empirical model has been developed which can predict the vortex strength and fan face distortion for any configuration. Under headwind conditions a new vortex formation criterion has been established which also includes contours of vortex circulation. An a priori prediction of the vortex strength under headwind conditions has also been developed which considers the approaching and intake induced vorticity sources, the latter of which is determined empirically. Good agreement is found between the model and the experimental dataset. The rolling ground plane experiments demonstrate significant sensitivities illustrating that the correct conditions must be simulated properly.